Analyzing the impact of higher education on economic growth in Qatar - Mrad, Jessica Abou; Fayad, Nour Mohamad; Zeineh, Hala (Edelweiss Applied Science and Technology, 2025)
The complex interaction of higher education and economic growth has, in recent years, become a significant issue of international concern (Hanushek & Woessmann, 2020). In this regard, higher education and economic development in Qatar, which is undergoing one of the most rapid economic transformations, are discussed in terms of dynamics, challenges, and opportunities. This research encompasses the role of the State of Qatar’s educational system in highlighting its strengths, besides challenges faced by learners, especially those aggravated by the COVID-19 pandemic, through critical areas like research-based educational practices, increased parental involvement in education, and professional development of educators. The data series employed in the present study are from the years 2000 to 2022 and test key variables, including graduate employment rates, GDP, income inequality, foreign direct investment, industry-academia collaboration, innovation, educational attainment, and labor force skills. As such, it becomes evident that about 66.5% of the variability in the GDP of Qatar can be explained by the type of these predictors, whereas on the positive axis, employment rates, labor force skills, and GDP are positively related. On the other hand, negative correlations between industry-academia collaboration and educational attainment do suggest that more nuanced policy interventions will be called for to maximize the benefit of higher education for economic growth. The findings should have useful implications for policymakers in pursuit of increasing the role of the education sector in Qatar’s economic development.